REPRODUCTIVE PERFORMANCE OF FOUR VARIETIES OF INDIGENOUS ASEEL CHICKEN UNDER DIFFERENT REARING SYSTEMS - M. S. Rehman1; A. Mahmud; S. Mehmood; T. N. Pasha; J. Hussain; M. T. Khan; M. Shafiq; M. I. Abbas; M. A. Akram (Journal of Animal and Plant Sciences, 2020)
A study was undertaken to investigate the effect of three rearing systems (free range, semi-intensive and confinement) on reproductive performance in four varieties of indigenous Aseel chicken (Lakha, Mushki, Peshawari and Sindhi). A total of 192 adult birds (168 females and 24 males), 48 from each variety, were subjected to 3 rearing systems under Randomized Complete Block Design (RCBD) in a factorial experiment. Data regarding reproductive performance [settable eggs (%), fertility (%), hatch of fertile (%), hatchability (%), embryonic mortality (%) and A-grade chicks (%)] were recorded from 31 to 46 weeks of age. The collected data were analyzed by using ANOVA technique. The results demonstrated improved settable eggs, fertility and hatchability in hens reared under confinement and semi-intensive rearing systems. Among different varieties, Sindhi and Peshawari hens depicted higher settable eggs (95.41±0.54) and A-grade chicks (59.36±2.57), respectively. Interaction of rearing systems and varieties clearly indicated maximum settable eggs in both Sindhi and Peshawari hens reared under confinement rearing system. Fertility and hatchability were greater (P≤0.05) in Sindhi hens under semi-intensive rearing system. The highest (P≤0.05) A-grade chicks (63.59±4.68) were found in Peshawari hens under semi-intensive rearing system. From the findings, it can be concluded that confinement and semi-intensive rearing systems remained comparatively better with respect to settable eggs, fertility and hatchability. Both Sindhi and Lakha varieties of Aseel hens can be raised in semi-intensive rearing system as they demonstrated better performance with respect to settable eggs and A-grade chicks.
Keywords: Aseel chicken; Reproductive performance; Rearing systems